Representasi Identitas Perempuan Berhijab dalam Bingkai Media Massa: Kajian Literatur Sistematis - Efi Fadilah; Nunik Maharani Hartoyo; Putri Amalia Kunaefi (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
Women who wear hijab are one of the marginalized groups. Islamic-majority countries like Indonesia even have a long history of hijab, which was even banned during the Orde Baru era. The phenomenon of women wearing hijab has become a concern for society, religious communities, the government, and including academics, especially in media studies. This research discusses how the development of the study of the representation of women wearing hijab in mass media in Indonesia. Using Ridley's systematic literature review method to collect 10 scientific literature documents related to the representation of women wearing hijab in the mass media. 10 scientific literature documents then underwent data extraction with 6 categories, namely: focus of discussion, media objects, methods and data analysis, theories used, research results, and suggestions. The results of the study suggest that mass media construction of women wearing hijab depends on the ideology of the media so that the media's point of view varies. There are media that see hijab as a symbol of piety, fashion, domestic sphere, stereotypes, challenges, and freedom of human rights. This indicates that the issue of women wearing hijab can still be studied in mass media that adhere to different ideologies.